2019
DOI: 10.5005/jp-journals-10071-23232
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Empathy with Patient among Healthcare Provider Students: A Structural Equation Modeling Study

Abstract: ContextIn medicine and health care, empathy is a very important component of relationship between a physician or healthcare provider and patients.AimsThis study was designed to investigate the factors affecting empathy with patient among healthcare provider students using structural equation model.Settings and designCross-sectional studyMaterials and methodsIt was a cross-sectional study to examine the conceptual model based on JSE-HPS. Three hundred ninety-eight students of School of Nursing and Midwifery, Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Previous studies identified "perspective-taking," "compassionate care," and "standing in patient's shoes" programs that provide healthcare students with information about the relevance of empathy and its role in patients treatment. 15,16 Organizational culture, personal and interpersonal relationships, and demographic characteristics are all highly linked to increased empathy. The authors were interested in conducting a comprehensive review of determinants related to empathy with a focus on pharmacy students.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies identified "perspective-taking," "compassionate care," and "standing in patient's shoes" programs that provide healthcare students with information about the relevance of empathy and its role in patients treatment. 15,16 Organizational culture, personal and interpersonal relationships, and demographic characteristics are all highly linked to increased empathy. The authors were interested in conducting a comprehensive review of determinants related to empathy with a focus on pharmacy students.…”
Section: Methodsmentioning
confidence: 99%
“…Concerning the factors affecting empathy with patients among medical students, the prior study identified “perspective-taking”, “compassionate care” and “standing in patient's shoes” programs providing medical students to familiarize them with the importance of empathy and its role in care [ 19 ]. However, organizational culture, personal and interpersonal, and demographic factors are strongly implicated in inhibiting empathy [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the current issue of Indian Journal of Critical Care Medicine , Fatemeh Zahra Karimi and Mahbubeh Abdollahi present their study on factors affecting empathy with patient among students of nursing and midwifery. 2 Since this study addresses how the constructs are related to other constructs, this editorial attempts at finding a connect with empathy in a wider humanistic perspective.…”
mentioning
confidence: 99%